The Costs of Training Medical Parasitology and Mycology Students at Kerman University of Medical Sciences - Reza Goudarzi; Majid Fasihi Harandi; Mohammad Tasavon Gholamhoseini; Mohammad Ebrahimipour (Kerman University of Medical Sciences, 2021)
Background: Training of expert human resources is one of the main and basic objectives of developed countries. One of the important challenges for attainment of this objective is shortage in funding and financial resources. This is while medical branches, due to being specialized and requiring vast practical courses, need spending considerable financial costs for training competent students.Objectives: The present study aimed to estimate the costs of training medical parasitology and mycology students at Kerman University of Medical Sciences.Methods: This was a descriptive research. The data collection tool was a form designed by researchers using various resources. Educational and non-educational costs of the academic year of 2017-2018, with a top-down approach, were analysed to estimate the costs of training and educating post-graduate students. Analyses were made using Microsoft Excel 2013 software.Results: The costs of educating master students in parasitology, Ph.D. students in parasitology, and master students in mycology in the academic year of 2017-2018 were 11,144, 18,365, and 7,821 USD, respectively. Forty-five percent of the total of educational costs was allocated to training Ph.D. students in parasitology alone, and a major share (81%) of these costs had been paid to human resources.Conclusion: Our findings indicated that the financial costs of training and educating students in the parasitology and mycology fields are high, needing the prompt attention of the policymakers of the national medical education system.